An optimized device for staining electron microscopy grids. (January 2014) - Mathieu, E; Benmlih, K; Fabre, R; Hemmerle, J
Abstract Proper staining of grids is critical for transmission electron microscopy (TEM). Staining must be done as quickly as possible using minimal reagents and with consideration for the environment. We developed a new device for efficient staining of multiple TEM grids. We studied reagent evaporation, rinsing volume, flow rate and re-use of uranyl acetate, and provide here a procedure for efficient staining using the new device. Our device permits TEM grids to be stained with less reagent than alternative staining apparatuses; staining requires a total volume of 260 μl for five grids. Reagent evaporation is less than 6% even if used at 37° C. Moreover, our staining apparatus reduces chemical waste and shortens experiment time by staining several grids simultaneously. Our staining device is a compromise between time-consuming single grid processing and expensive commercial devices that consume large amounts of reagents.